Fintech Analysis of Personal Finance App Usage among Millennials - Tika Handayani; Rifky Lana Rahardian; Eva Yuniarti Utami; Apriani Riyanti; Ahmad Rizani (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2024)
This study aims to analyse the influence of Fintech on the use of personal finance applications in the millennial generation. The research method used in this study is the survey method. The survey was conducted using a questionnaire distributed to millennial respondents who use personal finance applications. The data collected through the survey will be analysed quantitatively to identify usage trends, feature preferences, and the impact of personal finance apps on individual financial behaviour. The results show that millennials have a high adoption rate of personal finance apps. They tend to use these apps to track expenses, organise budgets, and conduct financial transactions. In-app personalisation features are highly valued by millennials, as it allows them to tailor the experience according to individual needs and preferences. However, data security and privacy remain key concerns in the use of personal finance apps. Personal finance apps have great potential in helping millennials manage their finances more effectively. However, serious attention should be paid to data security and user privacy. Therefore, it is recommended that personal finance app providers continue to improve their security systems and privacy practices. In addition, it is also necessary to educate users on the importance of protecting their personal information when using personal finance apps.